A retrospective assessment of the clinical efficacy of different internal fixation methods in the treatment of distal fibula fractures in the elderly. Issue 43 (28th October 2022) - Zhao, Wenhai; Wang, Qian; Cui, Zhenhai; Yue, Zhenshuang; Hu, Zhongqing; Zeng, Linru; Xin, Dawei; Tang, Yanghua; Tang, Dezhi
Abstract : An ankle fracture is a fracture of the distal tibia or fibula that forms the ankle joint, usually associated with ligament and soft tissue injury, and is a common type of lower limb fracture and one of the most common types of fracture in the elderly. Although ankle fractures are one of the most common injuries seen by orthopedic trauma surgeons, there is no uniform protocol for the diagnosis and treatment of ankle fractures in the elderly, and there are many controversial indications for surgery. The aim of this study is to assess the clinical efficacy of different internal fixation methods in the treatment of distal fibular fractures in the elderly, in an effort to improve the rational selection and application of clinical acts. A retrospective analysis was performed on 68 cases of patients who suffered an ankle fracture and were treated with different internal fixation methods according to the fracture types and individual differences in distal fibula fractures. The postoperative therapeutic effect assessment was performed in terms of clinical examination, imaging evaluation, and AOFAS ankle-hind foot function scoring. There was no unhealed bone, ankle instability and loose/fractured internal fixation. Fracture healing time was 2.7 to 4.0 months (average 3.2 months). AOFAS score was 88.3 ± 6.2, of which, 34 excellent cases, 30 good cases, and 4 fair cases. Ankle activity dorsiflexion 6º 18º, average 15º; plantar flexion 26º 47º, average 37º. A good clinical efficacy could be achieved from the most appropriate individualized internal fixation for distal fibula fractures of elderly patients.